2023
DOI: 10.1186/s12967-023-04169-5
|View full text |Cite
|
Sign up to set email alerts
|

Gut microbiome combined with metabolomics reveals biomarkers and pathways in central precocious puberty

Abstract: Background Central precocious puberty (CPP) is a common disease in prepubertal children and results mainly from disorders in the endocrine system. Emerging evidence has highlighted the involvement of gut microbes in hormone secretion, but their roles and downstream metabolic pathways in CPP remain unknown. Methods To explore the gut microbes and metabolism alterations in CPP, we performed the 16S rRNA sequencing and untargeted metabolomics profilin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 43 publications
0
5
0
Order By: Relevance
“…Li et al performed analysis of proteomics and metabolomics in girls with CPP and found some key differential proteins and metabolites, including MMP9, SPP1, CDC42, POSTN, COL1A1, BMP1, and phosphocholine (16:1(9Z)/16:1(9Z)) (18). Huang et al performed 16S ribosomal RNA (rRNA) sequencing and untargeted metabolomic profiling of CPP patients; it was revealed that nitric oxide synthesis and Streptococcus were closely associated with CPP (19). Different from these studies, in this study, we conducted metabolomic analysis of fecal samples of clinical PP girls and animal models and further validated the role of significantly changed metabolites at the animal level.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…Li et al performed analysis of proteomics and metabolomics in girls with CPP and found some key differential proteins and metabolites, including MMP9, SPP1, CDC42, POSTN, COL1A1, BMP1, and phosphocholine (16:1(9Z)/16:1(9Z)) (18). Huang et al performed 16S ribosomal RNA (rRNA) sequencing and untargeted metabolomic profiling of CPP patients; it was revealed that nitric oxide synthesis and Streptococcus were closely associated with CPP (19). Different from these studies, in this study, we conducted metabolomic analysis of fecal samples of clinical PP girls and animal models and further validated the role of significantly changed metabolites at the animal level.…”
Section: Discussionmentioning
confidence: 88%
“…Huang et al. performed 16S ribosomal RNA (rRNA) sequencing and untargeted metabolomic profiling of CPP patients; it was revealed that nitric oxide synthesis and Streptococcus were closely associated with CPP ( 19 ). Different from these studies, in this study, we conducted metabolomic analysis of fecal samples of clinical PP girls and animal models and further validated the role of significantly changed metabolites at the animal level.…”
Section: Discussionmentioning
confidence: 99%
“…Among them, girls with CPP showed increased alpha diversity in their gut microbiota, significant increases in bacteria, such as Alistipes , Klebsiella , and Sutterella , and enhanced inter-bacterial correlations [ 7 ]. Another cross-sectional study demonstrated significant differences in gut microbiota and metabolites between children with CPP and healthy controls, with the Streptococcus genus potentially serving as a candidate molecular marker for CPP treatment [ 103 ]. Similarly, in an observational study, fecal samples from 25 girls with idiopathic CPP and 23 healthy girls were subjected to 16S rDNA sequencing to compare microbial compositions between the groups.…”
Section: Precocious Pubertymentioning
confidence: 99%
“…Moreover, several observational studies have shown associations between nitric oxide synthesis and the progression of precocious puberty [ 103 ]. Functional predictions of the gut microbiota in girls with CPP show increased nitric oxide synthesis and positive correlation with FSH and insulin in children with CPP [ 7 ].…”
Section: Interaction and Potential Mechanisms Between Gut Microbiota ...mentioning
confidence: 99%
See 1 more Smart Citation